Naturally occurring drug resistance associated variants to hepatitis C virus direct-acting antiviral agents in treatment-naive HCV genotype 1b-infected patients in China. Issue 19 (May 2017) - Li, Zhanyi; Zhang, Ying; Liu, Ying; Shao, Xiaoqiong; Luo, QiuMin; Cai, Qingxian; Zhao, Zhixin
Abstract : Abstract: The direct-acting antiviral agents (DAAs) have drastically improved the prognosis of hepatitis C virus (HCV) patients. However, the resistance-associated variants (RAVs) to DAAs may hamper treatment. There was a lack of data on the prevalence of pre-exist RAVs in Chinese HCV-infected patients. We performed nested PCR assays on 74 HCV genotype 1b-infected patients to amplify HCV viral regions of NS3, NS5A, and NS5B to investigate the prevalence of RAVs to DAAs in treatment-naive HCV genotype1b-infected patients in China. The mutations A156S, T54S, and D168Y of the NS3/4A region were found in 18.33% (11/60), 6.67% (4/60), and 1.67% (1/60) of the successfully amplified cases. Mutations Q30R, L31M, and H58P of the NS5A region were confirmed in 57.63% (34/59), 1.69%(1/59), and 86.44% (51/59) of the cases. Mutations C316N, S365A, M414L, M423I, Y448H, I482T, I482 V, V494L, P495S, and V499A of the NS5B region were detected in 100% (60/60), 3.33% (2/60), 5.88% (3/51), 1.96% (1/51), 1.96% (1/51), 5.88% (3/51), 1.96% (1/51), 3.92% (2/51), 5.88% (3/51), and 15.69% (8/51) of cases, respectively. Naturally occurring RAVs to DAAs pre-exist in treatment-naive Chinese HCV genotype 1b-infected patients and the characteristic is different from that in Europe and the United States. Clinicians should consider RAVs upon the introduction of DAA-based antiviral therapy. Abstract : Supplemental Digital Content is available in the text